Fig. 1 in Helminth Diversity In Teleost Fishes From The Area Of The Ukrainian Antarctic Station "Akademik Vernadsky", Argentine Islands, West Antarctica - Kuzmina, T. A.; Dykyy, I. V.; Salganskij, O. O.; Lisitsyna, O. I.; Korol, E. M.; Kuzmin, Yu. I. (Zenodo, 2021)
Fig. 1. Proportion (%) of five parasite taxa found in teleost fish off the area of the UAS "Akademik Vernadsky", Argentine Islands, West Antarctica. Published as part of Kuzmina, T. A., Dykyy, I. V., Salganskij, O. O., Lisitsyna, O. I., Korol, E. M. & Kuzmin, Yu. I., 2021, Helminth Diversity In Teleost Fishes From The Area Of The Ukrainian Antarctic Station "Akademik Vernadsky", Argentine Islands, West Antarctica, pp. 251-264 in Zoodiversity 55 (3) on page 256, DOI:10.15407/zoo2021.03.251, http://zenodo.org/record/6455979